REVITALISASI PASAR SUNGAI BARU DENGAN PENDEKATAN PENCIPTAAN RUANG PUBLIK - Nurizan, Nurizan; Khaliesh, Hamdil; Nurhamsyah, M. (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2026)
Sungai Baru Market is a traditional market located in Sungai Baru Village, Teluk Keramat District, Sambas Regency. Privately owned, the market serves the local community by offering various goods such as snacks, groceries, household items, building materials, and more. In 2016, the market was struck by a fire, which led to a significant decrease in visitor numbers. In response, local youth took the initiative to bring vibrancy back to the market by organizing community events and competitions, including boat races, ngael undang (shrimp fishing), the Sungai Baru Fair, outdoor film screenings, and others. However, the market lacked the necessary infrastructure to properly support such activities. This final project proposes the revitalization of Sungai Baru Market through a public space approach. Public space, in this context, refers to an environment that facilitates social interaction and accommodates both individual and communal activities. The design method used in this project is based on the five-step design process introduced by Snyder & Catanese (1989) in their book Introduction to Architecture, which includes: initiation, preparation, proposal, evaluation, and implementation.. The outcome of the project is a redesigned market divided into two main zones: the market zone and the public space zone. Sungai Baru Market is classified as a Type C market. The public space zone includes visitor parking, a waterfront area, spectator stands, a food court, a children’s play area, a mini field, a dock, and boat parking facilities. These features are intended to support local activities and cultural events in Sungai Baru Village, such as boat races and performing arts showcases.